2021
DOI: 10.1111/tid.13721
|View full text |Cite
|
Sign up to set email alerts
|

Potential donor characteristics and decisions made by organ procurement organization staff: Results of a discrete choice experiment

Abstract: Organ procurement organizations (OPOs) evaluate referrals for deceased organ donation in the United States. Efforts to expand the donor pool, such as the HIV organ policy equity (HOPE) Act that permits transplants from HIV-positive donors to HIVpositive recipients, can only succeed if OPOs pursue referrals. However, relatively little is known about how OPO staff evaluate referrals. To better understand this process, OPO staff completed a discrete choice experiment to quantify the relative importance of seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Perceived barriers and disincentives to pursue HIV D+ at the OPO level have been identified in prior studies. 15 , 16 A study by Predmore et al, 16 which included in-depth interviews with 20 OPO staff members, identified OPO concerns regarding HIV disclosure to next-of-kin and fear of HIV infection to procurement staff. In practice, these concerns should not be barriers to donation and procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived barriers and disincentives to pursue HIV D+ at the OPO level have been identified in prior studies. 15 , 16 A study by Predmore et al, 16 which included in-depth interviews with 20 OPO staff members, identified OPO concerns regarding HIV disclosure to next-of-kin and fear of HIV infection to procurement staff. In practice, these concerns should not be barriers to donation and procurement.…”
Section: Discussionmentioning
confidence: 99%
“… 17 In a study of OPO decisions to pursue HOPE donors, the number of potential organs that could be recovered was the most important attribute. 15 Thus, the possibility of having multiple organs utilized from a donor would likely influence OPOs to evaluate and procure organs from more HIV D+ referrals.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma both within and outside of the healthcare system continues to be a barrier, impacting potential HOPE donors, recipients, and transplant centres [51 ▪ ]. More specifically, there seems to be preference for donors without HIV over donors with HIV in Organ Procurement Organizations (OPOs) which may be due to the small pool of candidates with HIV that can accept these organs, potential concerns about acquisition costs given that only kidney and livers are being transplanted currently, and HIV stigma within the healthcare system [51 ▪ ]. Education about HIV organ donation, interventions to reduce HIV stigma, and partnerships with HIV organizations might help further break down the barriers that prevent the HOPE Act from reaching its full potential [50].…”
Section: Opportunities To Expand Human Immunodeficiency Virus D+/r+ S...mentioning
confidence: 99%
“…Another study by the same group involved a discrete choice experiment completed by the staff from 36 OPOs in the United States to quantify the relative importance of donor characteristics on the decision to pursue a theoretical donor. 117 Of the 7 attributes, organ and tissue potential were the most influential; an HIV-positive donor needed to have the potential to donate 2 additional organs to be preferred to an HIV-negative donor.…”
Section: Introductionmentioning
confidence: 99%